Numerical Simulation and Hazard Analysis of Debris Flows in Guxiang Gully, Tibet, China - Tang, Jinbo; Liu, Chen; Mao, Jiajie; Wang, Hao (Frontiers in Earth Science, 2022)
Guxiang Gully, located in Bome county in southwest Tibet, China, is a right-bank tributary of the Purlung Tsangpo River. Hanging glaciers are widely distributed upstream of the gully, and a large number of moraines can cause debris flows triggered by run-offs generated by the rainstorm and melting water of glaciers deposited in this gully. The debris flow in the Guxiang Gully can frequently pose a serious threat to the Sichuan–Tibet highway. Due to the lack of field observation data, in this study, the flood discharge method combining the run-off generated by rainstorms and melting water of glaciers was employed to determine the magnitudes of debris flows under once-in-a-century, once-in-two-century, and once-in-three-century flood return periods. Furthermore, a numerical simulation is implemented to determine the maximum flow depth and velocity of the debris flow in each grid cell and the inundated debris flow area in Guxiang Gully with different return periods. Subsequently, each grid cell’s maximum flow depth and velocity are used to assess buried hazards and impact hazards, respectively. The integrated hazard could be calculated by combining the buried hazard and the impact hazard. The result shows that the hazard of the top of the fan and Purlung Tsangpo River affected by the debris flow is highest, and the debris flow is likely to block the Purlung Tsangpo River.